Neural Dynamics of Reaching Following Incorrect or Absent Motor Preparation - Ames, K. Cora (2014)
Moving is thought to take separate preparation and execution steps. While preparing, neural activity in primary motor and dorsal premotor cortices achieves a state specific to an upcoming action, but movements are not performed until the execution phase. We investigated whether this preparatory state (more precisely, prepare-and-hold state) is required for movement execution using two complementary experiments. We compared monkeys’ neural activity during delayed and non-delayed reaches, and in a delayed reaching task in which the target switched locations on a small percentage of trials. Neural population activity bypassed the prepare-and-hold state both in the absence of a delay and if the wrong reach was prepared. However, the initial neural response to the target was similar across behavioral conditions. This suggests that the prepare-and-hold state can be bypassed if needed, but there is a short-latency preparatory step which is performed prior to movement even without a delay.